Effect of co-electrospinning system on morphology and oil adsorption of helical nanofibers. Issue 21 (November 2022) - Teng, Defang; Zeng, Yongchun
In this study, inspired by cucumber tendrils, nanofibers with helical morphology are fabricated in co-electrospinning systems with different spinneret configurations. Poly(m-phenylene isophthalamide) (Nomex) and thermoplastic polyurethane are chosen as the two components in co-electrospinning. Using simulation and experimental methods, the electric field distribution and the morphology of nanofibers from the three co-electrospinning systems are analyzed. The helical nanofibers generated from the off-centered spinneret co-electrospinning system possess a helical shape with larger curvature and show higher tensile strain. In addition, the helical nanofibers show an oil adsorption capacity up to 79.3 g g −1 and high oil retention (91%). This study may help control helical fiber morphology and extend the applications of helical materials.